On the Economic Health of Vietnam’s Construction Industry - Nguyen, Tristan; Doan, Trung Dung (Archives of Business Research, 2018)
This paper analyzes the economic health of Vietnam’s construction industry. The sample data have been collected from 32 construction companies listed on Ho Chi Minh Stock Exchange during 2013 to 2014. Their financial reports have been taken into account to examine the business condition by using the Altman Z-score Model and the Emerging Market Model. In these two models, the impact of Growth, Tangibility, Debt Ratio, Size and Cash Conversion Cycle are proved to be negative in relation with the firm’s performance in the original Z-sore. We find out in our analysis that the Emerging Market Model is the more appropriate model for assessing the health of Vietnam’s construction firms. In addition, further hypothesis tests are conducted to provide a regression analysis of the correlation between the Z-score and the five factors mentioned above. The regression has revealed that none of these factors has positive or negative impacts on Vietnam’s construction enterprises.